CAUSES OF MECHANICAL INTESTINAL OBSTRUCTION IN ADULTS - Hadi, Ain ul; Aman, Zahid; Batool, Iram; Khan, Mazhar; Khan, Shehzad Akbar; Ahmad, Siddique; Khattak, Jamshed Alam (Journal of Postgraduate Medical Institute, 2011)
Objective: Material and Methods: Results: Conclusion: The causes of intestinal obstruction are variable in different parts of the world. Tuberculosis was the leading cause of dynamic intestinal obstruction in this study. In this study of 93 cases, 100% patients presented with pain and abdominal distension. Other symptoms were less frequent. Males were 50 (53.76%) and females 43 (46.24%) with a male to female ratio of 2:1.72. Tuberculosis (36.55%) was the leading cause of mechanical intestinal obstruction followed by carcinoma of the large gut (22.58%) and postoperative adhesions (21.51%). Five (5.37%) patients had obstructed herniae and four (4.31%) had malignancy of the small gut. Three (3.22%) patients were with Meckle's diverticulum while 2(2.15%) each had appendicular adhesions, intussusception and sigmoid volvulus. This case series study was conducted at surgical C unit, of Lady Reading Hospital Peshawar, Pakistan from July 2006 to June 2007. In this study a total of 93 patients were included; who underwent exploratory laprotomy. These patients were diagnosed on the basis of clinical history, examination and radiological findings. After resuscitation, exploratory laprotomy was performed to confirm the diagnosis and relieve the obstruction. Laprotomy findings were recorded and where necessary specimen was sent for histopathology for definitive diagnosis. To investigate the causes of mechanical intestinal obstruction in adults at surgical C unit Lady Reading Hospital Peshawar.